Moderasi Beragama Lintas Agama dalam Perspektif Hukum Islam - Agus Sholahudin Shidiq; Farida Isroani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Greetings are one of the opening expressions in communication. How can communication run smoothly, let alone build harmony between religious communities, if greetings as a means of greeting non-Muslims are prohibited? The East Java MUI's appeal, addressed specifically to officials not to say interfaith greetings at official events, has become controversial and polemic in many circles. From cyberspace to the real world, this issue is widely discussed. Apart from the many parties who are against this appeal, there are also quite a few parties who are pro. People who oppose this appeal argue that the interfaith greeting, which has long been practiced by officials when delivering remarks or speeches at official events which are not only attended by Muslims but also adherents of other religions, is an attitude of tolerance. between religious communities and has become a culture. Because human nature is to always want to live in goodness and peace. To realize this nature of mutual peace, a practical relationship is needed that can bring all humans together in a state of calm and peace. So that the word greeting becomes a prayer that humans are granted protection from all disasters and dangers that can befall them.